Membingkai Good Corporate Governance Amal Usaha Muhammadiyah dalam Kerangka Amanah - Hafni, Diska Arliena; Harventy, Gina (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
This paper examines the concept of Good Coorporate Governance that can be applied in the Amal Usaha Muhammadiyah (AUM). As one of Indonesia’s largest Muslim organization, Muhammadiyah has thousand of Amal Usaha. Amal Usaha efforts serves a packaged for Persyarikatan to realize the ideals of Muhammadiyah. Amal Usaha can be actually be used, as a means to gain profit, but if it is pulled back to the Amal Usaha purposes of Muhammadiyah profit oriented, that initially will have to support the activities of Muhammadiyah is non profit. It is then differentiate amal usaha efforts with other companies. So we need a concept of governance on Amal Usaha of Muhammadiyah is it not just referring to the principles of fairness, transparency, accountability and responsibility. However, this need frame of ‘amanah’ to harmonize efforts with Amal Usaha purposes sacred ideals of Muhammadiyah.